VERBS OF PERCEPTION, THINKING, SPEAKING FROM THE POINT OF VIEW OF PSYCHOLOGY - Назарова Манзура Насруллаевна (American Journals, 2024)
This article deals with verbs of perception of various types.
Keywords: Perception, experience, speech, function, thinking, psychology.